مفهوم الخطاب الديني المعاصر وضوابطه - زيد, مليكة (University of Eloued جامعة الوادي, 2020)
تناول البحث موضوعًا في غايةِ الأهمِّية له علاقة بمنهج الدَّعوة إلى الله تعالى، وله أثر كبير في معالجة المشكلات ومواجهة التَّحديات الرَّامية إلى كسر بيضة الإسلام سواء بالكلمة أو الكتابة متمثِّلة في الخطاب الدِّيني وقضية تجديده، ونظراً للتقدُّم العلمي الهائل والتقني المتطور الذي تعيشه البشرية والتَّنوع المذهل لوسائل الاِتصال الحديثة وكثرتها جاءت هذه الورقة البحثية لتقديم رؤية في تجديد الخطاب الدِّيني المعاصر منْ حيث المفهوم والضوابط والشروط، بهدفِ الكشفِ عن طبيعة الخطاب الدِّيني في ظلِّ هذا التَّطور، والتعرف على أهم الضَّوابط الشَّرعية والأخلاقية التي تحسم الخطاب الدِّيني وتَضبُطه ،والتي من خلالها يستطيع التَّعايش مع الواقع ، وقدْ اتَّبعت الباحثة المنهج الوصفي في هذا البحث متوصِّلة إلى أنَّ عملية التَّجديد لا تتوقَّف ولا تنتهي لكونها قضية مستمرَّة ومتجدِّدة ،وكان الخطاب الدِّيني في مصاف هذا التَّجدد، وتجديده يمثل تجديد آلياته و طريقتة في التَّواصل مع الآخر منْ حيث الأسلوب والحوار. Abstract: The research dealt with a very important topic related to the method of the call to Allah and its great impact on solving problems and facing the challenges which seek for destroying Islam, namely, the religious discourse and its renewal. Due to the tremendous scientific and technological advancement experienced by mankind and the amazing diversity of modern means of communication, this research paper presented a vision in the renewal of contemporary religious discourse in terms of concept, rules and conditions in order to reveal the nature of the religious discourse in light of this development, and to identify the most important legal and ethical rules that establish and discipline the religious discourse, through which it can coexist with reality. The researcher has followed the descriptive approach in this research concluding that the process of renewal does not end because it is a continuous and recurring issue, and that the renewal of the religious discourse should be based on the renewal of its mechanisms and way of communication with the other in terms of style and dialogue. Keywords: religious discourse, renewal, rules, contemporary renovation
Keywords: الكلمات المفتاحية : الخطاب الدِّيني ، التَّجديد ، الضَّوابط ،المستجدات المعاصرة.